Crystallization of rapidly quenched ribbons on the base of Fe₈₂Si₂B₁₆ under isothermal annealing - Brud'ko, O.P.; Nosenko, V.K.; Zakharenko, M.I.; Skljarov, Yu.P. (Functional Materials, 2005)
The crystallization kinetics of the amorphous alloys on the base of Fe₈₂Si₂В₁₆ has been studied under isothermal annealing using magnetometric method. The apparent crystallization activation energy of Еₐ and Avrami exponent n have been determined. The
admixtures of Ni and Мо have been shown to influence weakly on the values of Еₐ and n.
The apparent activation energy of crystallization for the ribbons produced using industrial
raw materials coincides within the experiment accuracy with that for the alloys of identical composition produced from chemically pure components. It has been also ascertained that the n value is determined mainly by the chemical composition of alloy rather than by the thickness of the rapidly quenched ribbon. Магнитометрическим методом исследована кинетика кристаллизации аморфных сплавов на основе Fe₈₂Si₂В₁₆ в процессе их изотермических отжигов. Определены энергия активации кристаллизации Еₐ и показатель Аврами n. Показано, что добавки Ni и Мо слабо влияют на значения Еₐ и n. Энергия активации кристаллизации для лент, изготовленных с использованием промышленных лигатур, в пределах погрешности совпадает с соответствующим значением для сплавов того же состава, изготовленных из химически чистых компонентов. Установлено также, что величина n зависит, главным образом, от состава аморфного сплава, а не от толщины быстрозакаленной ленты. Магнiтометричним методом дослiджено кiнетику кристалiзацiї аморфних сплавiв на основi Fe₈₂Si₂В₁₆ в процесi їх iзотермiчних вiдпалiв. Визначенi енергiя активацiї кристалiзацiї Еₐ i показник Аврамi n. Показано, що добавки Ni i Мо слабко впливають на значення Еₐ i n. Енергiя активацiї кристалiзацiї для стрiчок, виготовлених з використанням промислових лiгатур, в межах похибки експерименту спiвпадає з вiдповiдним значенням для сплавiв того ж складу, виготовлених з хiмiчно чистих компонентiв. Встановлено також, що величина n залежить, головним чином, вiд складу аморфного сплаву, а не вiд товщини швидкозагартованої стрiчки.